Effect of Polymer-Modified Bitumen and Reclaimed Asphalt Pavement on The Physical Properties of Bitumen - Odubela, C. A.; H., Yaacob; M. N. M., Warid; K. J. A., Karim; M. K. A., Mohd Lazi; N. H. M., Kamaruddin; Putra Jaya, Ramadhansyah; Z. H., Al-Saffar; M. I. K. A., Rahim (IOP Science, 2024)
The high cost of road construction due to the energy required for new material production and the environmental impact necessitates the use of reclaimed asphalt pavement (RAP) and other waste materials. This paper examined the effect of using RAP with a PET additive as a rejuvenator. PET additive (2%) was added to the virgin binder (VB) of 60/70 penetration grade to form a Polymer modified bitumen (PMB). RAP percentages used were 30, 40, and 50%, respectively. The physical properties were examined using the penetration, softening point, and ductility. The results show that the physical properties of RAP were improved by utilizing Rap binder (RB) and PMB mix ratio. The penetration and ductility values increased by 46.4% and 66.7%, respectively, with the PMB (30): RB (70) ratio blend, compared to RB: VB blend. This suggests a reduction in brittle behavior and less stiffness with the addition of PMB in the blend, enhancing the flexibility of the RAP. Although both mixtures blended with RB exhibited softening points within the acceptable range, improved performance was observed with RB/PMB mix blend over RB/VB blend when used in hot asphalt mixture.